Adsorption studies for the removal of nitrate using chitosan/PEG and chitosan/PVA polymer composites. (February 2016) - Rajeswari, A.; Amalraj, Augustine; Pius, Anitha
Abstract: This paper presents a study of the removal of nitrate ions using polyethylene glycol/chitosan and polyvinyl alcohol/chitosan composites were investigated. A series of batch experiments were conducted to examine the effects of contact time, adsorbent dosage and pH of the solution. Composite materials successfully adsorb nitrate from aqueous solutions at pH 3. Adsorption isotherm studies indicated that polymer composites satisfy Langmuir and Freundlich models. The rate of reaction follows pseudo-second-order kinetics. The adsorption capacities of PEG/chitosan & PVA/chitosan were found to be 50.68 and 35.03 mg g −1 respectively. The prepared adsorbents were characterized by Scanning electron microscopy (SEM), Energy dispersive analysis of X-rays (EDAX), Fourier Transform Infra-Red (FTIR), BET surface area and X-ray Diffraction (XRD). The results of the study indicated that polyethylene glycol/chitosan and polyvinyl alcohol/chitosan composites are useful materials for the removal of nitrate from aqueous solution.